“TO BE MACHO OR NOT TO BE MACHO, THAT IS THE QUESTION”: HOW MACHISMO IS RELEVANT TO DISCRIMINATION IN THE ROMANIAN AND SERBIAN HEALTH SECTORS - Ekrem TUFAN (Eastern European Journal of Regional Studies)
Health sector workers continuously provide services globally, regardless of their professional challenges. Such as the struggle against discrimination and racism. In this study, the existence of discrimination/racism against healthcare professionals was examined using the examples of Romania and Serbia. In the study, the MetaHuman Artificial Intelligence Program was used. As a result, it has been observed that there is no racism, however discrimination against atheist doctors in every country exists regarding religious beliefs. A further discovery is that survey participants from all countries favored the macho or the most beautiful doctor. Countries' decision-makers in education should ensure that extra information on this subject is added to education programs to prevent discrimination and/or racism. This research will extend to search discrimination view differences in the health sector between the Turkish minority in Germany and Turks living in Türkiye.